Respuesta :

Answer:

The difference between the given terms is

–73 – (–40) = –33.

The difference between the term numbers is 28 – 17 = 11.

Dividing –33 / 11 = –3.

The common difference is –3.

The recursive formula is the previous term minus 3, or an = an – 1 - 3 where a17 = -40

Step-by-step explanation:

The nth term of an arithmetic sequence is expressed as Tn = a + (n-1)d. The recursive formula for this sequence is Tn = 3Tn-1

Recursive formula

The nth term of an arithmetic sequence is expressed as:

Tn = a + (n-1)d
where

a is the first term

n is the number of terms

d is the common difference

If the 17th term is -40 and the 28th term is -73 hence;

a + 16d = -40
a + 27d = -73

Subtract

16d - 27d = -40 + 73
-11d = -33
d = 3

The required recursive function is given as:

Tn = dTn-1
Tn = 3Tn-1

Hence the recursive formula for this sequence is Tn = 3Tn-1

Learn more on recursive function here: https://brainly.com/question/489759

#SPJ5